Determinant of Sustained Growth in Emerging Markets: Indonesia - ., Gerson; Manurung, Adler Haymans; Eprianto, Idel; Hendayana, Yayan; Hidayat, Wastam Wahyu (Journal of Ecohumanism, 2025)
This research has aim to explore determinant of Sustained Growth in Emerging Markets which is Indonesia. This research has period of research of 2010 to 2023 using Manufacturing Company. Model panel data is used to estimate coefficient model. This research found that ROA, NPM, exchange rates, the covid-19 pandemic and company size have a significant influence on business sustainability. On the other hand, current ratio and sales growth have no significant effect on business sustainability. This study also reveals that the interaction of company size turns out to show significant differences in the company's business sustainability (ROA and NPM). However, the difference does not appear significant for current ratio and sales growth. These empirical results imply the urgency to optimize less productive assets into more profitable sectors to improve business sustainability as well as the importance of managerial strategies in managing the profitability of large companies to remain aligned with business sustainability goals.